Efficient identity-based fully homomorphic encryption over NTRU - Ran DUAN; Chun-xiang GU; Yue-fei ZHU; Yong-hui ZHENG; Li CHEN (Tongxin xuebao)
Fully homomorphic encryption is the best solution for solving privacy concerns for data over cloud so far,while large public key size is a general shortcoming for existing schemes.First,by introducing the concept of Kullback-Leibler divergence,an identity-based public key scheme over NTRU lattice with modified ciphertext form was proposed.Analysis on parameter setting showed its small key size and ciphertext size,and experiments revealed its high computational efficiency.Second,with the idea of approximate eigenvector,an improved method to convert the scheme into an identity-based fully homomorphic encryption one was put forward to further reduce ciphertext size.Compared with existing schemes,the converted scheme not only abandons evaluation keys to make it fully identity-based,but also has smaller keys and ciphertext,which results in higher computational and transmission efficiency.